FORMS AND METHODS OF INCREASING THE ACTIVITY OF WOMEN IN PRODUCTION - Abdukhalilova Nafisa Shonazarovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In our country, a wide range of work is being carried out on increasing the socio-political activity of women and girls, creating conditions for their realization of their abilities and opportunities in various spheres and sectors, ensuring unconditional observance of their rights and legitimate interests, comprehensive support of motherhood and childhood, as well as strengthening the Family Institute. Every time the term "woman" is heard in the century in which we found ourselves, we think about struggle, strength and labor. Over time, it has been mentioned about the virtues around women who have developed in their favor, but all the same it is necessary to overcome many obstacles. Taking into account the best results of the next and women's day, let's talk more about the role of women and mothers in society. In this article discusses about forms and methods of increasing the activity of women in production.